Optimization of Docosahexaenoic Acid (DHA) Production and Improvement of Astaxanthin Content in a Mutant Schizochytrium limacinum Isolated from Mangrove Forest in Thailand - Wassana Chatdumrong; Wichien Yongmanitchai; Savitree Limtong; Wanchai Worawattanamateekul (Agriculture and Natural Resources, 2007)
Polyunsaturated fatty acids including DHA are essential dietary fatty acids. At present, fish oils are a major source, but an alternative supply is needed because of increasing demand and fish dwindling stocks. This need might be satisfied using a thraustochytrids found in mangrove forests of Thailand and identified by 18S rDNA sequencing as either Schizochytrium limacinum or Thraustochytrium aggregatum. S. limacinum was tested in various culture conditions to find the optimal yield of DHA. This culture medium contained 7.5% glucose, 0.5% peptone, 0.5% yeast extract (with either 0.25% soybean meal or 1% skimmed milk) and 0.75% sea salt at 20-30°C. The C:N ratio was about 15:1. The culture was mutated using NTG and one isolate showed high DHA content and also a red pigment identified as astaxanthin by TLC and HPLC. Astaxanthin synthesis peaked on day 6 - 10 of incubation in medium containing 2% glucose using shaking flasks at 180 rpm, 25°C, 2 kLux light intensity with a 18:6 h light:dark periods. Six days of incubation yielded the highest yields of both DHA (224.6 mg/l) and astaxanthin (8.9 μg/ml of medium). These results suggested that this microorganism could provide a commercial source of this valuable lipid and pigment.